The COVID Retirement Boom and Personal Finance: How can we save and protect? - Ahn, Hoseok (Technium Social Sciences Journal, 2023)
Granting periodic income payments to retirees, the Social Security system is undoubtedly an essential part of American retirement financing. Indeed, 90% of American retirees receive Social Security and 57% of its beneficiaries depend on it as the major source of income. While Social Security is indispensable to American retirement financing, retirees ought not to be unduly dependent on it, as current demographic changes imperil the institution’s regulation. Over the last decade, the United States retirement population increase rate has been 33.79%, approximately seven times that of the labor force population. This pattern jeopardizes the Social Security system by raising its cost disproportionately to its income. Thus, if such a demographic trend continues, the Social Security System will no longer be able to provide retirees with income. Confronting the possibility of systemic failure of the Social Security system, I will argue in this paper that retirees must take responsibility for their own finances and voluntarily produce income through investing in two asset classes – REITs and bond ladders. My research will discuss two advisable investment plans: REITs and bond ladders. Each method will be evaluated on its safety, periodicity of income, and consistency in the income quantity. Furthermore, for each method, I will examine its upsides and downsides. This research discusses the transfer of financial responsibility from the Social Security system to individual retirees. It proposes retirement plans that the members of our community can practice to produce income.